"No.69. Pedralbes. Cuartel General. Camiones blindados en la casa Girona". Series of 2 photos. Copied from CNT collection
"No.69. Pedralbes. Cuartel General. Camiones blindados en la casa Girona". Series of 2 photos. Copied from CNT collection.